A Survey of Current Practice in Operative Management of Testicular Torsion in Poland - Aneta Piotrowska-Gall; Piotr Stępień; Przemysław Wolak (MDPI AG, 2023)
The primary aim of this study is to evaluate heterogeneity in the current management of testicular torsion (TT). A secondary aim is to investigate incidences of recurrent torsion and the methods used for primary fixation. An online multiple-choice questionnaire comprising 10 questions was distributed to paediatric surgeons and urologists. There were a total of 99 questionnaires distributed to representatives from 39 paediatric surgery and urology departments in Poland. The majority of participants agreed on fixation of the torsed testicle (98%). Use of sutures was reported by 95% of surgeons: absorbable by 48%, non-absorbable by 42%, and 4% using both. There was no consensus on the number of sutures. The contralateral testicle was always fixed by 69%, with 28% fixing it only in case of necrosis and amputation of the torsed testicle, and the remaining 2% never fixing the contralateral side. In case of negative scrotal exploration, 18% of surgeons would still fix the testis. The recurrence of torsion after prior fixation was identified by eight of the participants. The most commonly reported primarily used technique was absorbable sutures. There is a general consensus on the fixation of torsed testicles; however, other aspects remain controversial. Based on the survey and the literature review, the use of non-absorbable sutures rather than absorbable sutures would be advisable.